2007
DOI: 10.1590/s1413-70542007000400010
|View full text |Cite
|
Sign up to set email alerts
|

Efeito de indutores de resistência sobre Meloidogyne exigua do cafeeiro

Abstract: A possibilidade de manejo de Meloidogyne exigua Goeldi, 1887, pela ativação de mecanismos de defesa no cafeeiro representa uma alternativa potencialmente útil no manejo desse patógeno. Com este trabalho, objetivou-se avaliar a eclosão e mortalidade de juvenis do segundo estádio (J2) de M. exigua na presença de produtos indutores de resistência e avaliar o efeito do acibenzolar-S-metil (ASM, Bion®) na indução de resistência do cafeeiro (Coffea arabica L.) 'Catuaí- 144' contra M. exigua. A eclosão e mortalidade … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
15
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 17 publications
(14 reference statements)
1
15
0
3
Order By: Relevance
“…However, the results of our study were not consistent with these findings, since only Experiment 2 showed difference between application times. ASM was not effective in controlling Meloidogyne exigua Goeldi in coffee cultivar Catuaí 144, and no significant difference was observed between the treatments for final population, number of galls and reproduction factor variables 90 days after inoculation (Salgado et al, 2007). Some authors draw attention to the factors that could cause variations in the results obtained for inducing nematode resistance, that includes dosage, treatment timing, application method and cultivar genetic resistance (Owen et al, 1998;Owen et al, 2002;Molinari & Baser, 2010).…”
Section: (Experiments 2)mentioning
confidence: 99%
See 4 more Smart Citations
“…However, the results of our study were not consistent with these findings, since only Experiment 2 showed difference between application times. ASM was not effective in controlling Meloidogyne exigua Goeldi in coffee cultivar Catuaí 144, and no significant difference was observed between the treatments for final population, number of galls and reproduction factor variables 90 days after inoculation (Salgado et al, 2007). Some authors draw attention to the factors that could cause variations in the results obtained for inducing nematode resistance, that includes dosage, treatment timing, application method and cultivar genetic resistance (Owen et al, 1998;Owen et al, 2002;Molinari & Baser, 2010).…”
Section: (Experiments 2)mentioning
confidence: 99%
“…This may be due to the time required to induce the plant's resistance mechanisms, since various studies have shown that ASM does not affect hatching, survival and nematode penetration of host roots (Chinnasri et al, 2003;Salgado et al, 2007;Molinari & Baser, 2010), but it does impair nematode development and reproduction (Chinnasri et al, 2003;Molinari & Baser, 2010).…”
Section: (Experiments 2)mentioning
confidence: 99%
See 3 more Smart Citations